2016
DOI: 10.1097/igc.0000000000000758
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrated Lymphocytes, Macrophages, and Dendritic Cells in Endometrioid Adenocarcinoma of Corpus Uteri as Potential Prognostic Factors: An Immunohistochemical Study

Abstract: In conclusion, our study showed for the first time that the low level of expression of markers for tumor-associated T lymphocytes (CD3), NK cells (CD57), macrophages (CD68), and an increased expression of markers for tumor-associated B lymphocytes (CD20) and dendritic cells (S100) in endometrioid adenocarcinoma progression lead to poor survival outcome. The associated criteria of these immune cells may be used as predictive factors in the diagnosis of tumor progression. Our study indicates that local antitumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…All cases were stained with antibodies to identify CD3 (T cells), CD20 (B cells), CD57 (NK cells), CD68 (macrophages), and S100 (dendritic cells) by immunohistochemistry. Expressions of CD3, CD57, and CD68 were significantly higher in archived tissue in the good outcome group (p < 0.001) compared with the poor outcome group, whereas there was no significant difference between CD20 and S100 in the two groups [35]. High levels of immune cells, notably CD3 T cells in cancer tissue, and good outcome is consistent with the findings of other investigators [36][37][38].…”
Section: Cellular and Molecular Regulation Of Endometrial Cancer Progsupporting
confidence: 89%
See 1 more Smart Citation
“…All cases were stained with antibodies to identify CD3 (T cells), CD20 (B cells), CD57 (NK cells), CD68 (macrophages), and S100 (dendritic cells) by immunohistochemistry. Expressions of CD3, CD57, and CD68 were significantly higher in archived tissue in the good outcome group (p < 0.001) compared with the poor outcome group, whereas there was no significant difference between CD20 and S100 in the two groups [35]. High levels of immune cells, notably CD3 T cells in cancer tissue, and good outcome is consistent with the findings of other investigators [36][37][38].…”
Section: Cellular and Molecular Regulation Of Endometrial Cancer Progsupporting
confidence: 89%
“…These investigators evaluated archived histological material of 82 patients with stage I to III EA, with good (survival) and poor (disease progression and death) outcome. Outcome status was retrospectively determined from their patient study database [35]. All cases were stained with antibodies to identify CD3 (T cells), CD20 (B cells), CD57 (NK cells), CD68 (macrophages), and S100 (dendritic cells) by immunohistochemistry.…”
Section: Cellular and Molecular Regulation Of Endometrial Cancer Progmentioning
confidence: 99%
“…Our research revealed that MELF-pattern in specific cancer stroma fibrosis has immune cells infiltration where TAT and TAM cells are found at a reduced number. Previously, we described a correlation between differential MELF-pattern and survival of patients with EA [11]. In the current study, we present that changes in immune cells infiltration in cancerous stroma may also contribute to EA progression and may be a manifestation of aggressive potential of MELF-pattern in cancer development.…”
Section: Resultssupporting
confidence: 64%
“…Between each step, the sections were washed twice with Tris-buffered solution for 5 min each. The reaction product was visualized with 3,3-diaminobenzidine (DAB) staining for 5 min, followed by Mayer's hematoxylin counterstaining [10,11].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Zinovkin and Pranjol ( 41 ) studied 82 patients with endometrioid adenocarcinoma at stages I–III and demonstrated that the downregulation of lineage-specific markers in T lymphocytes (CD3), NK cells (CD57) and macrophages (CD68), and the upregulation of markers in B lymphocytes (CD20) and DCs (S100) in endometrioid adenocarcinoma, indicated a poor clinical outcome. Furthermore, as cancer-associated fibroblasts ( 42 ) and adipocytes ( 43 ) serve an important role in the genesis of an immunosuppressive microenvironment and in the malignant progression of hyperplasia, their functions in EC need to be studied further in the future.…”
Section: Immunosuppressive Microenvironment In Ecmentioning
confidence: 99%